ANALISIS LINTAS TERBANG ROKET MULTI-STAGE RKN200 - Sasongko, Rianto. A; Jenie, Yazdi. I; Poetro, Ridanto. E (Indonesian Journal of Aerospace, 2011)
This paper deals with a trajectory analysis of RKN200 multi-stage rocket system. The implementation of a multi-stage configuration means that a separation process has to be taken within the flight phase. The separation process is basically a transition process from a phase with booster as initial/launch propulsion to that with sustainer as the propulsion for the rest of flight time. RKN200 is a multi-stage rocket developed by LAPAN Indonesia for defence applications. In a multi-stage rocket development process, stage separation becomes a critical phase which should be considered carefully, since this phase will significantly affect the entire flight performance of the rocket. In this paper, the trajectory of RKN200 is analyzed in various cases with separation process included. The separation stage is modeled as a discrete process, i.e. by applying a sudden change on the rocket parameters values at the time of separation. In addition to that, impulsive force and moment which occur as a result of the separation ignition will also introduced into the mathematical model of the rocket dynamics, such that their influence to the rocket flight variables can be counted and computed . The modeling, simulation, and analysis of the flight trajectory are conducted using a simulation software already developed for rocket dynamic and performance analysis. Some simulation results are presented and analyzed to evaluate the RKN200 flight trajectory in some flight settings and conditions, and also to observe the effect of stage separation process on the rocket flight.